Comprehensive Evaluation of Role of Metabolic Biomarkers in Atherosclerotic Plaque Microenvironment: The Enigma in Its Origin and Regression - Anshuman Pradhan; S. Siddharth Rao; A. Nyna Sindhu (Indian Journal of Vascular and Endovascular Surgery)
Atherosclerosis, a lipid driver chronic inflammatory pathophysiological process, has been the centerpiece of cardiovascular disease (CVD), cerebrovascular accidents, and other arterial pathology-related morbidities. It has simultaneously been a source and a result of many intrinsic and extrinsic governing factors. Early identification of individuals at high risk of CVD is fundamental to tailor targeted treatment and preventive strategies. This mandates an ongoing need to identify biological markers that are useful to stratify CVD risk. Several classical risk factors for atherosclerosis have been identified and validated decades ago, namely hypercholesterolemia, hypertension, diabetes mellitus, and smoking, resulting in development of various risk prediction models, namely Framingham Risk Score. However, there are major limitations to it, as closely 20% of CVD patients actually do not display one of these risk factors and 40% only display one risk factor. This highlights the necessity to discover or identify novel biomarkers to complement these conventional risk factors. Many new biomarkers for inflammation (e.g., high-sensitivity C-reactive protein and growth differentiation factor-15) and plaque instability/rupture (e.g., myeloperoxidase and matrix metalloproteinases [MMPs]) have recently emerged, although their exact pathological role and the marker biochemistry are often not yet completely understood. Moreover, several microRNAs have been recently identified as biomarkers, which could potentially play a leading role in cardiovascular risk stratification prognostication. These biomarkers could be used in the clinic in conjunction with other clinical parameters, such as established risk factors, patient history, and physical findings. The histopathology and intravascular imaging show that a stable atheroma undergoes one of several phenotypic changes to become destabilized and at risk for occlusive luminal thrombosis. An unstable plaque associated with clinical luminal thrombosis manifests one of several phenotypes, including erosion, fibrous cap rupture, nodular calcification and rupture, and cap rupture overlying single or multiple layers of previous cap “rupture and repair. “The phenotypes are characterized by altered hemodynamic shear stress, prominent endothelial denudation and dysfunction, smooth muscle cells phenotypic changes, fibrous cap remodeling, expansion, and growth of the vasa vasorum, activation of adventitial and perivascular adipose tissue cells, and alteration in chronic inflammation and lipid deposition. Here comes the need for molecular and bioengineering identification techniques to evaluate the existing high levels of proinflammatory markers, cytokines, chemokines (interleukin [IL]-6, MMP-9, and IL-15) for improvement in early diagnosis, better optimization in risk assessment stratifiction, and corresponding better management/ prognosticating evidences indicating enhanced outcomes.” A simplified approach is to consider a two-stage paradigm, first – atheroma formation from a preatheroma lesion, and then, second – conversion of the atheroma to a complicated plaque. These studies will further improve the comprehension of the timeline of atherosclerotic plaque formation and its conversion from stable to unstable plaque.